Angiogenesis inhibitors in cancer therapy: mechanistic perspective on classification and treatment rationales - El-Kenawi, Asmaa E (Blackwell Publishing Ltd, 2013)
Angiogenesis, a process of new blood vessel formation, is a prerequisite for tumour growth to supply the proliferating tumour with oxygen and nutrients. The angiogenic process may contribute to tumour progression, invasion and metastasis, and is generally accepted as an indicator of tumour prognosis. Therefore, targeting tumour angiogenesis has become of high clinical relevance. The current review aimed to highlight mechanistic details of anti-angiogenic therapies and how they relate to classification and treatment rationales. Angiogenesis inhibitors are classified into either direct inhibitors that target endothelial cells in the growing vasculature or indirect inhibitors that prevent the expression or block the activity of angiogenesis inducers. The latter class extends to include targeted therapy against oncogenes, conventional chemotherapeutic agents and drugs targeting other cells of the tumour micro-environment. Angiogenesis inhibitors may be used as either monotherapy or in combination with other anticancer drugs. In this context, many preclinical and clinical studies revealed higher therapeutic effectiveness of the combined treatments compared with individual treatments. The proper understanding of synergistic treatment modalities of angiogenesis inhibitors as well as their wide range of cellular targets could provide effective tools for future therapies of many types of cancer.